The effect of basalt fiber addition on cement concrete: A review focused on basalt fiber shotcrete - Liu, Qianqian; Song, Pengfei; Li, Lianwei; Wang, Yuzhong; Wang, Xuhao; Fang, Jian (Frontiers in Materials, 2022)
Basalt fiber, as a natural silicate fiber, has excellent engineering performance in high and low Shotcrete was widely used in tunnel lining, slope support, coal mine roadway and other projects. With the continuous development of shotcrete technology, scholars found that adding fiber to shotcrete would greatly improve the performance of shotcrete. Compared with traditional plain shotcrete and steel fiber shotcrete, shotcrete incorporated with basalt fiber can dramatically improve the bending resistance, toughness and durability, therefore effectively improving the engineering performance of concrete structure, such as lining support. This paper summarized and discussed the mechanical properties, early age performance, durability and practical applications of basalt fiber shotcrete (BFSC) materials. Meanwhile, it focused on the engineering performance improvement and enhancement mechanisms of basalt fiber as a mineral admixture into shotcrete, and assessed the deficiencies existing in the current research. Eventually, the suggestions and prospects for future BFSC related research were proposed.